Severe Gestational Gigantomastia: from Mastectomy to Staged Autologous Breast Reconstruction. A Case Report. (September 2021) - Hassayoune, Noureddine; Mhallem Gziri, Mina; Lentini, Audrey; Chrelias, Theodoros; Hammer, Jennifer; Berlière, Martine; Lengelé, Benoît; Coyette, Maude
Summary: Gestational gigantomastia (GGM) is a rare condition characterized by a massive overgrowth of breast tissue during pregnancy. Surgical sanction may be required when conservative measures fail. In this study, we report the case of a 29-year-old woman who presented with an evolutive GGM responsible for physical and emotional distress, despite medical treatment. A multidisciplinary decision was made to induce delivery at 32 weeks. In the postdelivery period, the patient developed breast wounds, complicated with septic cardiomyopathy. An emergency bilateral mastectomy was then carried out, together with banking of both nipple-areola complexes. Thereafter, delayed bilateral 2-stage breast reconstruction was started at 12 months with subcutaneous tissue expanders, later on followed by implants removal and autologous reconstruction with bilateral deep inferior epigastric artery perforator flaps and bilateral nipple replantation.